Numerical Study of Vortex Dynamics in MVG-Controlled Hypersonic Flow at Mach 5.0 - Yan, Yonghua; Yang, Yong; Chen, Caixia; Baines, Demetric I (Engineering Science & Technology, 2025)
This study conducts a Large Eddy Simulation (LES) to investigate MVG-controlled hypersonic flow at Mach 5.0, analyzing flow structures such as momentum deficits and coherent vortex formations. Comparisons with Mach 2.5 flow reveal that increasing the Mach number makes ring-like vortices harder to distinguish. Under hypersonic conditions, stronger interactions occur between large vortex structures and boundary layer features, leading to greater vortex deformation. Proper Orthogonal Decomposition (POD) analysis is applied to explore flow dynamics, with the first two spatial modes capturing over 38% of the flow’s energy at Mach 5.0. The upper vortex structures exhibit a laminated pattern rather than a uniform flow distribution, indicating a shift in flow characteristics driven by vortex-boundary layer interactions. These findings inform the design of micro-vortex generators for enhanced boundary layer control in hypersonic vehicles, potentially improving aerodynamic stability and reducing thermal loads.